2020
DOI: 10.1186/s40001-020-00414-5
|View full text |Cite|
|
Sign up to set email alerts
|

The role of passive immunization in the age of SARS-CoV-2: an update

Abstract: The rapid spread of the corona virus pandemic is an existential problem for many people in numerous countries. So far, there is no effective vaccine protection or proven therapy available against the SARS-CoV-2 virus. In this review, we describe the role of passive immunization in times of the corona virus. Passive immunization could be a bridging technology to improve the immune defense of critically ill patients until better approaches with effective medications are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
16
0
4
Order By: Relevance
“…En una revisión sistemática (3) , los autores sugirieron que la efectividad del plasma de convalecencia para reducir la duración de la estadía hospitalaria depende de la administración temprana de la terapia, y es más probable que su uso como profilaxis sea beneficioso que el tratamiento de enfermedades graves. No conocemos el momento y la dosis óptimas de la terapia con plasma para convalecientes (9,19) . Por lo tanto, el reconocimiento rápido de los pacientes con COVID-19 que probablemente se enfermarán críticamente es vital para la administración de plasma convaleciente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En una revisión sistemática (3) , los autores sugirieron que la efectividad del plasma de convalecencia para reducir la duración de la estadía hospitalaria depende de la administración temprana de la terapia, y es más probable que su uso como profilaxis sea beneficioso que el tratamiento de enfermedades graves. No conocemos el momento y la dosis óptimas de la terapia con plasma para convalecientes (9,19) . Por lo tanto, el reconocimiento rápido de los pacientes con COVID-19 que probablemente se enfermarán críticamente es vital para la administración de plasma convaleciente.…”
Section: Discussionunclassified
“…Por lo tanto, la efectividad de la intervención con plasma convaleciente podría depender del nivel de anticuerpos neutralizantes del SARS-CoV-2 en el plasma del donante (11,18) . En las tomografías computarizadas de tórax se observaron diferentes grados de absorción de las lesiones pulmonares después de la transfusión (19) . Entre los hallazgos de laboratorio se encontraron la mejora de los valores de laboratorio de rutina y la función pulmonar, un aumento significativo en los títulos de anticuerpos neutralizantes (NaB) y el recuento de linfocitos, así como una disminución en la proteína C reactiva, alanina aminotransferasa y aspartato aminotransferasa después de una transfusión de plasma de convalecencia (20,21) .…”
Section: Discussionunclassified
“…These plasma fractions contain antibody against the SARS-CoV-2 virus, which will help further to the new patient to recover and fight against corona by activating passive immunity pathways. However, the efficacy of the treatment will depend on the methods such as whether the virus inactivation has been done or not, whether an immediate transfusion strategy has been used or not, whether the plasma has been collected at the right time or not (Fischer et al 2020, Rajendran et al 2020.…”
Section: Convalescent Plasma In Sars-cov-2mentioning
confidence: 99%
“…Current data have suggested that collected IgM and IgG antibodies from patients who have recovered from COVID-19 infection might be a therapeutic option for SARS-CoV-2, as they increase neutralizing antibodies ( 132 ). Until vaccines are discovered, passive immunization could be an alternative treatment strategy, particularly for high-risk groups, such as the elderly or patients with cancer ( 132 ).…”
Section: Immunizationmentioning
confidence: 99%
“…Current data have suggested that collected IgM and IgG antibodies from patients who have recovered from COVID-19 infection might be a therapeutic option for SARS-CoV-2, as they increase neutralizing antibodies ( 132 ). Until vaccines are discovered, passive immunization could be an alternative treatment strategy, particularly for high-risk groups, such as the elderly or patients with cancer ( 132 ). Keith et al ( 133 ) suggested the use of therapeutic plasma exchange (TPE) as a possible treatment for COVID-19 early in the clinical course, before patients proceed to septic shock or multiple organ failure.…”
Section: Immunizationmentioning
confidence: 99%